2019
DOI: 10.1097/01.aoa.0000575228.23198.ec
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Insertion of Large Bore Peripheral Intravenous Catheters in Maternity Patients for Postpartum Haemorrhage: A Cohort Study

Abstract: (Aust N Z J Obstet Gynaecol. 2018;58:548–552) In Australia, most women undergoing labor and vaginal delivery receive a peripheral intravenous catheter (PIVC) for any needed IV fluids, blood products or medications. While the smallest gauge catheter necessary is recommended by guidelines for intravenous access, many women receive a large-bore, 16 or 18 G, PIVC due to concerns about potential obstetric hemorrhage. Insertion of large-bore PIVCs can be very painful, especially when inserted in the back o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Relatively large‐gauge PIVCs were ubiquitously reported, with all women in our study receiving either a 16 or 18 g PIVC, consistent with previous local (Webster et al., 2018) and international research (Webster et al., 2019). In our study, PIVCs were inserted predominantly for medication or IV fluid administration: over half being in the back of the hand.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Relatively large‐gauge PIVCs were ubiquitously reported, with all women in our study receiving either a 16 or 18 g PIVC, consistent with previous local (Webster et al., 2018) and international research (Webster et al., 2019). In our study, PIVCs were inserted predominantly for medication or IV fluid administration: over half being in the back of the hand.…”
Section: Discussionsupporting
confidence: 90%
“…This study sought to describe and explore the practices of maternity healthcare professionals' decision‐making and practices about PIVC selection and use during labour and birth and measure the pain associated with this common procedure from the perspective of birthing women. It demonstrated that this somewhat ‘simple’ procedure is often unsuccessful (34%) and painful (3.3/10) (Webster et al., 2018, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations